Boundary discontinuous Fourier analysis of thick beams with clamped and simply supported edges via CUF - Canales, F.G. (2017)
This paper presents an analytical solution for static analysis of thick rectangular beams with different boundary conditions. Carrera's Unified Formulation (CUF) is used in order to consider shear deformation theories of arbitrary order. The novelty of the present work is that a boundary discontinuous Fourier approach is used to consider clamped boundary conditions in the analytical solution, unlike Navier-type solutions which are restricted to simply supported beams. Governing equations are obtained by employing the principle of virtual work. The numerical accuracy of results is ascertained by studying the convergence of the solution and comparing the results to those of a 3D finite element solution. Beams subjected to bending due to a uniform pressure load and subjected to torsion due to opposite linear forces are considered. Overall, accurate results close to those of 3D finite element solutions are obtained, which can be used to validate finite element results or other approximate methods.